Pengembangan Sistem Informasi Akuntansi Penjualan untuk Lembaga Pendidikan Studi pada LPIT Al-Furqan Yogyakarta - Edy Anan; M Sofyan Indrajaya (EBBANK, 2018)
This study aims to develop a sales accounting information system for educational institutions. Development efforts with case studies at Al-Furqan LPIT Yogyakarta. In contrast to some previous studies that use the subject of a trading company organization, this study uses the organization of educational institutions. Data collection techniques are carried out with methods of observation, interviews and documentation. System development is done by designing and using the SDLC method (System Development Life Cycle). Analysis of sales transactions using PIECES analysis.The results of research on LPIT Al-Furqan show that in addition to the development of sales accounting information systems, it is also necessary to develop Point of Sale (POS) and Payroll purchasing systems. This is intended to make the system more integrated. To overcome the lack of accounting softness for educational institutions, it is generally necessary to develop open source software on the market, so that it can be used by a wider organization of educational institutions